Pengukuran Variabel Makro dan Kinerja Keuangan Terhadap Perubahan Harga Saham - Munawarah Munawarah; Jeffry Suryono (Politeknik Ganesha Medan, 2019)
The aim of this study was to investigate the effect of inflation rate, interest rate, and net profit on stock prices at Metal companies listed on the Indonesia Stock Exchange in 2011-2015. The independent variables of this research were the rate of inflation, interest rates, and net profit. Dependent variable of this research was stock price. The research used a quantitative method. The populations were 16 metal companies listed in Indonesia Stock Exchange and there were 15 companies used as sample which taken by purposive sampling technique. The research data were the company's financial statements at the Indonesia Stock Exchange. The data were analized by multiple linear regression analysis. The results of this research indicated that Simultaneously, the rate of inflation, interest rates, and net profit had a positive and significant effect on stock prices. And partially, the inflation rate did not have a significant effect on stock prices, the interest rate did not have a significant effect on the price shares and net profit had a positive and significant effect on stock prices. The value of R square 0,289 shows that simultaneously the inflation rate, interest rate and net profit contributed to stock price only 28,9 %, and the remaining 71, 11% were affected by other variables not included in this study.